Development of application of grass sowing and grass crop rotations in organic agriculture of Ukraine in the first half of the ХХ-th century - V. D. Orekhivskyi (History of science and technology, 2018)
It is determined, that in the ХХ-th century organic agriculture was based on introduction of complex of scientifically reasonable natural and agro-technical measures, which was based on an ecological approach to its management. It is set that in the first half of the ХХ-th of century in Ukrain took place considerable distribution of the use of grass sowing and grass system of agriculture, worked out by an academician V. R. Viliams. It is found out, that cultivation of perennial legumes in grassland crop rotations provided for improvement of soil fertility, quality of agricultural products, improvement of the phytosanitary condition and the environment.